Role of Fibroblast Growth Factor-23 in Coronary Slow Flow Phenomenon Pathogenesis - Welly Oktaviandani; Taufik Indrajaya; Ali Ghanie; Erwin Sukandi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
The phenomenon of angina chest pain without significant epicardial coronary artery stenosis, but accompanied by a slowdown in coronary blood flow is often found in patients with symptoms of acute coronary syndrome who undergoing invasive coronary angiography. This phenomenon of slow coronary blood flow is then called the coronary slow flow phenomenon (CSFP). The pathogenesis mechanism of CSFP remains unclear. The pathogenesis of CSFP is thought to be multifactorial. Endothelial dysfunction, small vessel disease, inflammation, renin system angiotensin aldosterone, atherosclerosis are thought to be involved in the pathogenesis of CSFP. Cardiovascular disease incidence and death were associated with elevated levels of Fibroblast growth factor-23 (FGF-23). High levels of FGF-23 can lead to formation of blood vessel calcification, left ventricular hypertrophy, arterial stiffness, endothelial dysfunction, increased inflammatory markers and elevated levels of angiotensin II. It is suspected that FGF-23 has a role in this event other than as a regulator of bone and mineral metabolism. This literature review aims to determine the relationship between fibroblast growth factor-23 and the pathophysiology of CSFP. Based on the broad role of FGF-23, it is possible that FGF-23 is involved in the pathogenesis of CSFP.